Experiences and attitudes of hereditary cancer screening patients in a consumer directed testing model. Issue 3 (March 2021) - Greve, V.; Garner, M.; Odom, K.; Cooper, S.J.; East, K.M.
Highlights: Most IiP participants correctly interpreted result implications. Almost a quarter incorrectly interpreted a negative result as reduced cancer risk. Participants were satisfied with a written report and video for negative results. Eighteen percent of people would have preferred personalized results discussion. Abstract: Background: Since 2015, the Information is Power initiative has offered free and reduced cost hereditary cancer screening to the North Alabama population with a consumer-initiated model. Patients received pre-test and post-test education through a genetic counseling video. Positive results also received a call from a genetic counselor. Objective: We surveyed past Information is Power patients to assess if video education and electronic result delivery addressed the needs of a hereditary cancer screening population. Methods: An electronic survey was sent out to Information is Power patients who opted into research contact. The survey assessed participant knowledge, satisfaction with result delivery, and perceived uncertainty after receiving test results. Results: 213 participants completed the survey. Eighteen percent of participants would have preferred individual communication with a genetics specialist about their results. Over 99 % of survey participants correctly interpreted a positive result, while 73 % correctly interpreted a negative result. Overall, participants were certain about the impact of their genetic test results. Practice Implications: These findings support a model of population genetic testing and genetic counseling that is sustainable while meeting the educational needs of most participants. Observed misconceptions surrounding a negative result should be highlighted in future population screening patient resources to meet patient needs.